The Influence of Parasitic Infection on the Black Sea Whiting, Merlangius merlangus euxinus (Gadidae) - Skuratovskaya, E.N.; Yurakhno, V.M.; Zavyalov, A.V. (Вестник зоологии, 2013)
Morphophysiological and Biochemical ParametersComplex influence of infection by myxosporeans Myxidium gadi Georgevitsch, 1916; Ceratomyxa merlangi Zaika, 1966 and nematode Hysterothylacium aduncum (Rudolphi, 1802) on the morphophysiological and biochemical parameters of the Black sea whiting Merlangius merlangus euxinus (Nordmann, 1840) were studied. Significant decrease of spleenosomatic index and increase of hepatosomatic index in fish with average and high intensity of infection were found. The dependence of hepatic antioxidant enzyme activities on intensity of infection was observed. Increase of superoxidismutase, catalase, glutation-S-transferase activities in fish with average and high intensity of infection and decrease of peroxidase activity in specimens with average intensity of infection were shown. Исследовали комплексное влияние инвазии миксоспоридиями Myxidium gadi Georgevitsch, 1916; Ceratomyxa merlangi Zaika, 1966 и нематодой Hysterothylacium aduncum (Rudolphi, 1802) на морфофизиологические и биохимические показатели черноморского мерланга, Merlangius merlangus euxinus (Nordmann, 1840). Обнаружено снижение индекса селезёнки и увеличение индекса печени у рыб со средней и максимальной степенью заражённости. Выявлена зависимость активности антиоксидантных ферментов печени от интенсивности инвазии рыб. Показано снижение активности супероксиддисмутазы, каталазы, глутатион-Sтрансферазы у рыб со средним и высоким уровнем заражённости, повышение активности пероксидазы у особей со средней интенсивностью инвазии.